Numerical study on transport properties of the working mixtures for coal supercritical water gasification based power generation systems. (5th November 2019) - Yang, Xueming; Feng, Yiyu; Xu, Jiangxin; Jin, Jianghao; Liu, Yuanbin; Cao, Bingyang
Graphical abstract: Highlights: Viscosity of the H2 O/CO2 /H2 mixtures and H2 O/CO2 mixtures is investigated. Predicted values by EMD method and theoretical models are compared. Self-diffusion coefficient, H-bond number and RDF are calculated. The breakdown of Stokes–Einstein relation is found and discussed. Abstract: Viscosity of H2 O/CO2 /H2 mixtures or H2 O/CO2 mixtures is a vital transport property and required in the design of equipment for coal supercritical water gasification based power generation systems, however, no experimental data and studies have examined these viscosities in supercritical regions of water. In this paper, viscosity of these mixtures in supercritical regions of water is investigated by molecular dynamics method and different theoretical models. Moreover, the self-diffusion coefficient, radial distribution functions and H-bond number are also calculated via molecular dynamics simulations to make a better understanding of the temperature dependences of the viscosity of the mixtures in supercritical regions of water at a molecular level. The breakdown of Stokes–Einstein relation for the H2 O/CO2 /H2 mixture in supercritical regions of water is found and discussed. The prediction models and data put forth in this paper offer great value for practical application systems involving coal supercritical water gasification.